Development in the adoption of a national digital healthcare system and experience at taking new technology in use – changes from 2019 to 2022 - Pálsdóttir, Ágústa (Information Research an international electronic journal, 2024)
Introduction. The adoption of a national digital system for healthcare services in Iceland, and how people perceive their possibilities to adopt new technology is examined. Method. Surveys using random samples of people aged 18 years and older were conducted. The samples consisted of 1.800 people in 2019 and 1.200 in 2022. People 18-59 years old were reached by emails and 60 or older by phone. Response rates were 39% in 2019 and 45% in 2022. Analysis. The analysis is descriptive. Survey results from 2019 and 2022 are compared and differences by sex and age examined. Results. Considerable change was detected in use of the system for communication with health professionals tailored to participants health, while no increase was in obtaining information regarding issues not directly connected to people’s health history. The possibilities of adopting health technology were considered substantially better in 2022 than in 2019. Conclusion. People are likely to use digital healthcare systems when the situation requires, and they receive necessary support. It is important to consider the needs of those who are getting older for people to have equal opportunity to benefit from digital health information. Furthermore, reliable information offered by health professionals need to be promoted.